Visceral Adipose Tissue Volumetrics Inform Odds of Treatment Response and Risk of Subsequent Surgery in IBD Patients Starting Antitumor Necrosis Factor Therapy. Issue 5 (22nd July 2021) - Gu, Phillip; Chhabra, Avneesh; Chittajallu, Punya; Chang, Christopher; Mendez, Denisse; Gilman, Andrew; Fudman, David I; Xi, Yin; Feagins, Linda A
Abstract: Background: Data describing the effect of obesity on antitumor necrosis factor (anti-TNF) treatment response are inconsistent. Visceral adipose tissue (VAT) is a superior marker of adiposity to body mass index. However, its effect on treatment response is unclear. We aimed to evaluate the effect of VAT on anti-TNF treatment response. Methods: Inflammatory bowel disease (IBD) patients starting anti-TNF agents between January 1, 2009, and July 31, 2019, were included. 3-dimensional measurements of VAT volume and visceral fat index (visceral:subcutaneous adipose tissue ratio; VFI) were obtained from computed tomography (CT) scans. Subjects were categorized by predefined volume cutoffs (<1500cm 3, 1500–2999cm 3, ≥3000cm 3 ) and VFI (<0.33, 0.33–0.66, ≥0.67). Primary outcomes included a composite treatment response end point at 6 and 12 months. Secondary outcomes were surgery at 6 and 12 months. Multivariable logistic regression was used to calculate adjusted odds ratio (aOR) and 95% confidence interval (CI). Results: The final cohort included 176 patients. No significant differences in treatment response at 6 months was observed. At 12 months, compared with volume <1500cm 3, patients with volume 1500–2999cm 3 had higher odds of response (aOR, 3.52; 95% CI, 1.16–10.71; P = .023), whereas volume ≥3000cm 3 did not. Compared with VFI<0.33, VFI ≥0.67 had higher odds of surgery at 6 (aOR, 48.22; 95% CI, 4.73–491.57; P = .023) and 12 months (aOR, 20.94; 95% CI, 3.14–139.67; P = .004). Post hoc analysis suggested VAT may affect drug pharmacokinetics. Conclusions: We found VAT volume is associated with anti-TNF treatment response in a nondose dependent manner, and VFI may inform risk of surgery after anti-TNF initiation. If confirmed by prospective studies, VAT volumetrics are potentially useful biomarkers to inform IBD treatment decisions. Lay Summary: Visceral adipose tissue volume is associated with anti-TNF treatment response in a nondose response manner. Additionally, high visceral fat index is associated with significantly increased risk of early surgery after anti-TNF initiation.